Aplikasi Pupuk Kascing dan NPK dalam meningkatkan Produksi Tanaman Bawang Merah pada Tanah Ultisol - Sumini, Sumini; Wartono (Agriculture, 2025)
Red onions are a horticultural commodity that has high economic value. However, currently, red onion production often experiences a decline which can be caused by the low level of land fertility on ultisol soil. This study aims to analyze the vermicompost and NPK fertilizers in increasing the production of shallots on ultisol soil. The research was conducted in Muara Beliti Village, Musi Rawas Regency using the Factorial Randomized Block Design (RAK). The treatments tested were vermicompost K1 = 15 tons/ha, K2 = 25 tons/ha and K3 = 35 tons/ha. NPK fertilizer: N1 = 150 kg/ha, N2 = 200 kg/ha and N3 = 250 kg/ha. The results of the study showed that the application of vermicompost fertilizer with a dose of 15 tons/ha and NPK fertilizer with a dose of 150 kg/ha was able to increase the growth rate of plant height, increase the number of leaves and tuber diameter and had a very significant effect on the weight per tuber